2012
DOI: 10.1002/clen.201100320
|View full text |Cite
|
Sign up to set email alerts
|

River Water Pollution in Developed and Developing Countries: Judge and Assessment of Physicochemical Characteristics and Selected Dissolved Metal Concentration

Abstract: To compare water quality in rivers of developed and developing countries, a study based on physicochemical parameters and dissolved metals levels was conducted. Water samples were collected from selected sites in Dhaka, Bangladesh; Hokkaido and Osaka, Japan; Erdenet, Mongolia and West Java, Indonesia. Analysis of least significant differences revealed that most water quality parameters were within comparable low levels in both developed and developing countries. The dissolved metals concentrations were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 23 publications
1
46
1
1
Order By: Relevance
“…Alam et al (2007) found the mean values of pH, DO, BOD and COD lower in the Surma river than the present study. The mean values of pH, TDS, EC were lower but temperature were higher in the present study than the Shitalakhya, Turag and Bongshi rivers according to Sikder et al (2013).…”
Section: Physico-chemical Characteristics Of River Water and Sedimentcontrasting
confidence: 63%
“…Alam et al (2007) found the mean values of pH, DO, BOD and COD lower in the Surma river than the present study. The mean values of pH, TDS, EC were lower but temperature were higher in the present study than the Shitalakhya, Turag and Bongshi rivers according to Sikder et al (2013).…”
Section: Physico-chemical Characteristics Of River Water and Sedimentcontrasting
confidence: 63%
“…Sikder et al, 2013). The river floods frequently large parts of the town surrounding the river corridor (Budiyono, Aerts, Brinkman, Marfai, & Ward, 2014;Nuswantoro, Diermanse, & Molkenthin, 2014), especially in Central Jakarta, as a result of a flat terrain and of housing progressively encroaching the natural flood plain (Texier, 2008).…”
Section: Water Resources Land Use and Pollution Signaturesmentioning
confidence: 99%
“…The Cl − and BOD levels were measured using standard laboratory method. The detection limits were 0.02 mg/ L(PO [10,11]. Internal quality control was used in the measurement of the physicochemical parameters and dissolved metals in the samples from each region.…”
Section: Determination Of Water Quality Parametersmentioning
confidence: 99%